Changes in Students’ Motivation to Memorize the Quran: A Study at Quranic Higher Education Institutions in Indonesia - Engkizar, Engkizar; Jaafar, Azhar; Hamzah, Mohd Isa; Fakhruddin, Fathiyah Mohd; Oktavia, Gifa; Febriani, Afifah (Islamic Studies and Development Center in collaboration with Department of Islamic Education Universitas Negeri Padang, 2023)
In the early days of the Quran's revelation, there were only two reasons why the companions memorized the Quran: sincere intentions for Allah and to preserve the purity of the Quran. However, today, there are various motivations for memorizing the Quran. The purpose of this study is to determine the motivations for memorizing the Quran among students at Quranic colleges in Indonesia. To achieve this research objective, the author used two approaches, namely qualitative and quantitative. In the first stage, the author employed a qualitative approach involving twenty participants who were interviewed in depth. The participants were selected using purposive sampling techniques from the 2019, 2020, and 2021 cohorts. The collected data were then analyzed thematically using NVivo. The results of the first stage of the study identified nine motivations for students to memorize the Quran. These findings became the basis for the author to conduct the second stage of research using a quantitative approach. The nine motivations for memorizing the Quran were used as instruments, compiled in a Likert scale format to collect data on students’ motivations. This was done to confirm the findings in the first stage of research. In the second stage, the author involved 250 participants from a total of 1,500 students at Quranic colleges in Indonesia. The collected data were then analyzed using IBM SPSS Statistics 26 software. The results of the second stage showed consistency with the first stage. This study provides an overview of students’ motivations for memorizing the Quran at Quranic higher education institutions in Indonesia and shows that there has been a shift in the motives for memorization. Further studies need to revisit the issue of motivation in the context of restoring the purity of intention or making these nine motivations a reference for future research on Quran memorization.